Electrochemical device
By adopting a specific design of the separator and negative electrode sheet structure in lithium-ion batteries, the problem of insufficient discharge depth and volume expansion of the negative electrode material under large-scale discharge conditions is solved, and higher power supply capacity and low-temperature performance are achieved.
Patent Information
- Application Number
- CN202411954255.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The available discharge depth of existing lithium-ion batteries is insufficient under large-scale discharge conditions, and the silicon-containing negative electrode material collapses due to volume expansion during the charge and discharge cycle, affecting battery performance.
A diaphragm and negative electrode sheet structure with a striped ceramic layer and linear recess is adopted to control specific parameters (ratio of A and B) of the ceramic layer and negative electrode sheet to optimize the ion conduction efficiency and electrode structure stability of the electrochemical device.
The available discharge depth of electrochemical devices under large-scale conditions is significantly improved, the minimum residual power (SOC) level is reduced, the power supply capacity is enhanced, and good discharge performance is maintained under low temperature conditions.
Smart Images

Figure CN119833890A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrochemical device. Background Art
[0002] Lithium-ion batteries are widely used in 3C consumer products, electric vehicles, etc. As market competition becomes increasingly fierce, battery technology continues to develop towards larger capacity and higher charging power. Silicon (Si) is considered to be one of the most promising negative electrode materials because of its high theoretical specific capacity. The theoretical specific capacity of fully lithiated Si can reach 4200mAh / g (about 10 times that of graphite). However, because the lithium storage mechanism of silicon-based negative electrodes is an alloying reaction mechanism, silicon materials will undergo severe volume expansion during the lithiation process. During the battery charge and discharge cycle, repeated volume changes can cause the structure of the electrode material to collapse. At the same time, when lithium-ion batteries face the need for high-rate discharge, they often encounter the problem of insufficient available discharge depth, which limits their performance in certain application scenarios.
[0003] Therefore, there is an urgent need to develop a new battery to meet people's growing demand for high power and long-term discharge of battery systems. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide an electrochemical device which can alleviate the volume expansion caused by the silicon-containing negative electrode and at the same time can increase the discharge depth under high-rate discharge conditions.
[0005] In order to achieve the above object, the present invention provides an electrochemical device, the electrochemical device comprising a positive electrode sheet, a negative electrode sheet and a separator located between the positive and negative electrode sheets;
[0006] The diaphragm comprises a base film and a ceramic layer disposed on at least one side of the base film, wherein the ceramic layer comprises a plurality of stripes distributed at intervals and a plurality of spacing areas located between adjacent stripes, wherein the width of the stripes is A1 μm, the width of the spacing area is A2 μm, and A is A1 / A2;
[0007] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein a plurality of linear recesses are formed on the surface of the negative electrode active material layer on at least one side of the negative electrode sheet away from the negative electrode current collector, wherein the width of the linear recess is B1 μm, the depth of the linear recess is B2 μm, and B is B1 / B2;
[0008] The electrochemical device satisfies the relationship 3≤B≤11 and 5≤A×B≤50.
[0009] The present invention adopts the above technical solution to achieve the following beneficial effects:
[0010] In the electrochemical device provided by the present invention, the ceramic layer of the diaphragm is coated in a stripe shape, combined with a negative electrode sheet with a linear recess, and controlled to satisfy the above relationship, which can alleviate the volume expansion problem caused by the silicon-containing negative electrode sheet, and can also optimize the available discharge depth of the electrochemical device under high rate conditions, thereby reducing the minimum remaining charge (SOC) level required by the electrochemical device during effective discharge, thereby significantly enhancing the power supply capacity of the electrochemical device. In addition, the electrochemical device provided by the present invention also has good discharge capacity under low temperature conditions, and the battery performs well in cold environments.
[0011] The endpoints and any values of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Shown is a schematic structural diagram of a diaphragm in the present invention.
[0013] Figure 2 Shown is a schematic structural diagram of a diaphragm in the present invention.
[0014] Figure 3 Shown is a schematic structural diagram of a negative electrode sheet in the present invention.
[0015] Description of Reference Numerals
[0016] 11. Base film; 12. Ceramic layer; 13. Glue coating layer; 2. Linear concave portion; B1. Width of the linear concave portion; B2. Depth of the linear concave portion. DETAILED DESCRIPTION
[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0018] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.
[0019] In order to achieve the above object, the present invention provides an electrochemical device, the electrochemical device comprising a positive electrode sheet, a negative electrode sheet and a separator located between the positive and negative electrode sheets;
[0020] The diaphragm comprises a base film and a ceramic layer disposed on at least one side of the base film, wherein the ceramic layer comprises a plurality of stripes distributed at intervals and a plurality of spacing areas located between adjacent stripes, wherein the width of the stripes is A1 μm, the width of the spacing area is A2 μm, and A is A1 / A2;
[0021] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on at least one side surface of the negative electrode current collector. The surface of the negative electrode active material layer on at least one side surface of the negative electrode sheet away from the negative electrode current collector is provided with a plurality of linear recesses, the width of the linear recesses is B1 μm, the depth of the linear recesses is B2 μm, and B is B1 / B2.
[0022] The electrochemical device satisfies the relationship 3≤B≤11 (for example, 3, 4, 5, 6, 7, 8, 9, 10, 11) and 5≤A×B≤50 (for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50).
[0023] In the present invention, the separator is coated with a striped ceramic layer, which can enhance the migration rate of active ions in the electrolyte and optimize the distribution of the electrolyte inside the electrochemical device during the charge and discharge process; at the same time, the negative electrode sheet contains regularly arranged micropores caused by linear recesses, and when the ratio B of the width to the depth of the linear recesses is in the range of 3 to 11, the diffusion of lithium ions inside the electrode can be accelerated, the polarization phenomenon of the negative electrode under high current fast charging conditions is reduced, and the problem of lithium precipitation at the negative electrode is effectively prevented. It can also increase the contact area between the electrode and the electrolyte, and reduce the internal resistance of the electrochemical device. When the two work together and satisfy the above relationship, the charge and discharge capacity of the electrochemical device under high rate conditions is enhanced, the cycle performance of the electrochemical device under fast charging conditions is significantly improved, and the available discharge depth of the electrochemical device is improved, especially the available discharge depth of the electrochemical device under low temperature conditions is increased, and the minimum remaining charge (SOC) level required for the electrochemical device during effective discharge is significantly reduced, thereby significantly enhancing the power supply capacity of the electrochemical device under high rate working conditions. In the electrochemical device provided by the present invention, the ceramic layer of the diaphragm is coated in a stripe shape, combined with a negative electrode sheet provided with a linear recess, and controlled to satisfy the above relationship, which can also alleviate the volume expansion problem caused by the silicon-containing negative electrode sheet. When A×B is too small, on the one hand, it means that the stripe width A1 is narrow and the spacing area is wide, and the continuity deviation of the ceramic layer is easy to affect the contact interface between the diaphragm and the electrode sheet, affecting the ion conduction efficiency; on the other hand, it means that the line width B1 of the linear recess of the negative electrode sheet is small, and the purpose of significantly improving the ion transmission efficiency cannot be achieved, and thus the available discharge depth cannot be significantly improved. When A×B is too large, on the one hand, it means that the spacing width A2 is narrow, the stripe area is wide, and the liquid storage space that can be provided is limited, and the distribution of the electrolyte inside the electrochemical device during the charge and discharge process cannot be effectively optimized; on the other hand, it means that the width B1 of the linear recess is large, which will lead to a deviation in the consistency of the surface of the negative electrode sheet, and will also affect the contact interface between the diaphragm and the electrode sheet, affecting the ion conduction efficiency.
[0024] Those skilled in the art can select the width of the stripes and the width of the spacer according to the structure of different electrochemical devices and the base films of different materials. In some embodiments, A1 is 25 to 100, such as 25, 30, 40, 50, 60, 70, 80, 90, 100. In some embodiments, A2 is 6.7 to 50, such as 6.7, 10, 20, 30, 40, 50. There is no special requirement for the direction of the stripes, which can be parallel to the length direction of the diaphragm or perpendicular to the length direction of the diaphragm, or have a certain angle with the length direction of the diaphragm.
[0025] In some embodiments, A is 1 to 5, such as 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5. When A is within this range and the electrochemical device satisfies the relationship 3≤B≤11 and 5≤A×B≤50, the spacer area of the ceramic layer can provide more ion transmission channels and electrolyte storage space, effectively improving the migration rate of active ions. When A is too large, it will affect the storage capacity of the battery cell, and it is impossible to effectively optimize the distribution of the electrolyte inside the electrochemical device during the charge and discharge process, thereby affecting the charge and discharge performance of the electrochemical device; if A is too small, it will have an adverse effect on the heat resistance of the electrochemical device, thereby threatening the thermal safety performance of the electrochemical device.
[0026] The linear recesses on the negative electrode sheet can be prepared by laser marking, and regular micrometer-level holes are formed on the surface of the negative electrode active material of the negative electrode active material layer of the negative electrode sheet. The length of the linear recesses is not particularly limited and can be selected according to the arrangement of the linear recesses and the size of the negative electrode sheet.
[0027] In some embodiments, B1 is 80 to 100, such as 80, 85, 90, 95, 100. In some embodiments, B2 is 10 to 20, such as 10, 12, 14, 16, 18, 20. When the electrochemical device satisfies the relationship 3≤B≤11 and 5≤A×B≤50, and further satisfies that the width and depth of the linear recess are within this range, the available discharge depth of the electrochemical device can be further optimized, thereby reducing the minimum remaining charge (SOC) level required by the electrochemical device during the effective discharge process, thereby significantly enhancing the power supply capacity of the electrochemical device, and in particular, improving the charge and discharge capacity and low temperature cycle performance under low temperature conditions, and improving the performance of the electrochemical device in a cold environment.
[0028] like Figure 3 As shown, a plurality of linear recesses 2 are provided on the surface of the negative electrode active material layer on at least one side of the negative electrode sheet away from the negative electrode current collector. The width B1 and the depth B2 of the linear recess are as shown in FIG. Figure 3 shown.
[0029] In some embodiments, the thickness H of the stripes in the ceramic layer of the diaphragm is 0.5 μm to 5 μm, such as 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm. In the present invention, the thickness of the spacer region may be zero.
[0030] In some embodiments, the ceramic layer comprises 40 wt % to 96 wt % of a ceramic material, 3 wt % to 60 wt % of a binder, and optionally 0.7 wt % to 3 wt % of a dispersant.
[0031] In certain embodiments, ceramic material includes at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silicon dioxide, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, cerium oxide, zirconium titanate, barium titanate, and magnesium fluoride. The binder and dispersant can be conventional materials in the art, such as binders can include but are not limited to polyvinylidene fluoride, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of vinylidene fluoride-trichloroethylene, polyvinyl acetate, polyvinyl alcohol, polyethylene oxide, polyamide, polyacrylonitrile, acrylate polymers (such as polymethyl methacrylate), polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, styrene-butadiene rubber, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polytetrafluoroethylene or polyhexafluoropropylene. Dispersant can include but is not limited to at least one of ethylene oxide and polyvinyl pyrrolidone.
[0032] In some embodiments, the particle size Dv50 of the ceramic material is 0.1 μm to 2.5 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm. It is understood that the particle sizes of the ceramic material particles can be the same or different. When the particle size of the ceramic material is within this range, the liquid storage capacity of the diaphragm and the migration rate of lithium ions can be further improved, thereby improving the charge and discharge performance of the battery.
[0033] Dv50 refers to the particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 50%, which can be measured by a particle size analyzer.
[0034] In some embodiments, the base film has a thickness of 4 μm to 20 μm, such as 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, or 20 μm.
[0035] In some embodiments, the base film separator is a woven film, a nonwoven film, a polyolefin film, or a separator paper.
[0036] In some embodiments, the material of the polyolefin film includes at least one of polyethylene and polypropylene.
[0037] In one embodiment, the elongation at break of the base film in the transverse direction (TD) is 20% to 200%, such as 20%, 40%, 60%, 80%, 100%, 120%, 140%, 160%, 180%, 200%. The test method is to prepare the base film into a sample with a width of 15 mm along the TD direction, set the initial distance between the clamps of the tensile tester to 50 mm, and test at a tensile speed of 100 mm / min until the diaphragm breaks. The distance between the clamps at the time of break is recorded as L. TDmm, then the elongation at break in the TD direction = (L TD -50) / 50×100%.
[0038] In one embodiment, the elongation at break of the base film in the machine direction (MD) is 50% to 300%, such as 50%, 100%, 150%, 200%, 250%, and 300%. The test method is to prepare the base film into a sample with a width of 15 mm along the MD direction, set the initial distance between the clamps of the tensile tester to 50 mm, and test at a tensile speed of 100 mm / min until the diaphragm breaks. The distance between the clamps at the time of break is recorded as L. MD mm, then the elongation at break in the MD direction = (L MD -50) / 50×100%.
[0039] In one embodiment, the puncture strength of the basement membrane is 100 gf to 600 gf, such as 100 gf, 200 gf, 300 gf, 400 gf, 500 gf, and 600 gf. The test method is to flatten the basement membrane in a fixture and clamp it, and use a puncture needle with a diameter of Φ=1.0 mm and a spherical tip with a diameter of R=0.5 mm to puncture the membrane surface vertically at a rate of 100 mm / min until the membrane is punctured, and record the maximum value of the puncture force, which is the puncture strength of the membrane.
[0040] In one embodiment, the peel strength between the ceramic layer and the base film is 30 to 200 N / m, such as 30 N / m, 50 N / m, 100 N / m, 150 N / m, and 200 N / m. Test method: Take a stainless steel plate of a certain size, stick a double-sided tape in the center, and tear off the paper layer; take a coated diaphragm sample, and fit one side of the substrate to the upper surface of the double-sided tape; take a 15 mm wide 3M peeling tape, and the adhesive layer is close to the coating layer; use a rubber roller to roll back and forth naturally on the 3M peeling tape to ensure that the adhesive is evenly distributed; use a 180° peeling method and use a tensile tester to test the peeling force of the coating, then the peeling strength = peeling force / peeling tape width × 100%.
[0041] In some embodiments, the diaphragm further comprises a coating layer located on the surface of the base film and / or the surface of the ceramic layer. That is, the coating layer may be provided on one or both sides of the surface of the base film. Figure 1 As shown, when the base film 11 includes a one-side glue layer 13, the glue layer 13 can be disposed on the surface of the base film 11 away from the ceramic layer 12. Of course, if the diaphragm includes a one-side glue layer, the glue layer can also be disposed on the surface of the ceramic layer. Figure 2As shown, when the adhesive layer 13 is provided on both sides of the base film 11, one side of the adhesive layer 13 is located on the surface of the base film 11 away from the ceramic layer 12, and the other side is located on the surface of the ceramic layer 12. If the ceramic layer in the diaphragm is distributed on both sides of the base film, the adhesive layer is provided on both sides of the ceramic layer. The surface density of the coating on both sides of the base film can be the same or different.
[0042] In some embodiments, the difference in surface density of the coating on both sides of the base film is Δm, expressed in g / m 2 , Δm≤4, the surface density difference is, for example, 0g / m 2 , 0.5g / m 2 , 1g / m 2 , 1.5g / m 2 , 2g / m 2 , 2.5g / m 2 , 3g / m 2 3.5g / m 2 , 4g / m 2 The surface density difference Δm is controlled to be no more than 4g / m 2 When Δm is within this range, the adhesion and hardness between the diaphragm and the negative electrode are optimal, which alleviates the thickness change caused by silicon expansion, shortens the lithium ion transmission path, effectively improves the thickness expansion and cyclic lithium precipitation problems of lithium ion batteries during use, and improves the low-temperature charge and discharge performance and low-temperature cycle performance of electrochemical devices. However, when Δm exceeds this range, the surface density of the diaphragm coating layer is too large and the coating amount is too much, which is prone to sol blocking during the electrolyte immersion process, which will hinder the ion transmission efficiency and affect the charge and discharge capacity of the electrochemical device.
[0043] In some embodiments, the coating layer includes polymer particles.
[0044] In some embodiments, the average particle size of the polymer particles is 0.2 μm to 5 μm, for example, 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and 5 μm.
[0045] The average particle size of the polymer particles can be measured in the following manner: use an electrolytic emission scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.) to observe the surface of the porous layer at a magnification of 50,000 times. The image size at this time is 2.5μm×1.8μm. It should be noted that the number of pixels is 1,280 pixels×960 pixels, and the size of 1 pixel is 2nm×1.9nm. For the average particle size, draw a square or rectangle with the smallest area that completely surrounds one particle on the obtained image, that is, draw a square or rectangle with the end of the particle connected to the four sides of the square or rectangle. In the case of a square, the length of one side is set as the particle size, and in the case of a rectangle, the length of the long side (major axis diameter) is set as the particle size. For any 81 particles, measure their respective particle sizes, and set the number average as the average particle size. It should be noted that when more than 81 particles are observed in the captured image, the number average of any 81 particle sizes in the image is set as the average particle size. When 81 particles are not observed in the image, multiple images are captured and the number average of the total 81 particle sizes is set as the average particle size.
[0046] The polymer may be a polymer conventionally used in the art, such as, but not limited to, polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, acrylic copolymers (such as polymethyl methacrylate), polyolefins (such as polyethylene, polypropylene), polyacrylonitrile, polyethylene oxide, copolymers of fluoroolefin monomers (such as vinylidene fluoride-chlorotrifluoroethylene copolymers), copolymers of fluorine-containing olefin monomer units and olefin monomer units (such as vinylidene fluoride-ethylene copolymers), copolymers of fluorine-containing olefin monomer units and acrylic monomer units (such as vinylidene fluoride-acrylic acid copolymers), styrene-acrylonitrile copolymers, styrene-butadiene-acrylonitrile copolymers, styrene-vinyl acetate copolymers, styrene-vinyl acetate-pyrrolidone copolymers, and one or more of the modified compounds of the above copolymers.
[0047] In some embodiments, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material, in which silicon exists in the form of silicon particles.
[0048] In some embodiments, the average particle size D of the silicon particles Si The unit is nm and satisfies: 5≤D Si / A≤30, for example, it can be 5, 6, 8, 10, 15, 20, 25, 30. When the electrochemical device meets this range, the discharge depth of the electrochemical device can be effectively improved, the minimum remaining capacity (SOC) level of the electrochemical device that can effectively supply power can be reduced, and the long-term stable operation of the electrochemical device can be facilitated. SiWhen / A is too small, it means that the silicon particle size is too small. Too small particle size increases the mechanical stress of the material, causing structural damage and capacity decay. On the other hand, it means that A is too large, which will affect the liquid storage capacity of the negative electrode sheet and cannot effectively optimize the distribution of the electrolyte inside the electrochemical device during the charge and discharge process, thereby affecting the charge and discharge performance of the electrochemical device. Si When / A is too large, on the one hand, it means that the silicon particle size is too large and the specific surface area is too low, which has no significant effect on improving the ion conduction efficiency and is not conducive to improving the available discharge depth of the electrochemical device; on the other hand, it means that A is too small, which will have an adverse effect on the heat resistance of the electrochemical device, thereby threatening the thermal safety performance of the electrochemical device.
[0049] In some embodiments, the average particle size of the silicon material is 10 nm to 60 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, or 60 nm. When the electrochemical device satisfies: 5≤D Si / A≤30, and with the appropriate silicon particle size, smaller silicon particles can provide a larger specific surface area, improve the energy density of the electrochemical device, and increase the liquid storage space and ion transmission channels, which can significantly improve the ion conduction efficiency, increase the charge and discharge rate and cycle life, ensure that the electrochemical device has excellent cycle performance under low temperature conditions, and reduce the minimum SOC level that can be effectively discharged at low temperatures. However, too small a particle size will also increase the mechanical stress between the particles inside the negative electrode sheet, which can easily lead to structural damage and capacity decay of the electrochemical device.
[0050] D Si The size of the silicon particles can be observed through a transmission electron microscope (TEM), and the average particle size of 50 silicon particles can be calculated.
[0051] In some embodiments, the silicon content in the negative electrode active material is 3-20wt%, such as 3wt%, 5wt%, 10wt%, 15wt%, 20wt%. The design of the linear concave portion and the reasonable combination of silicon content can further improve the charge and discharge efficiency of the electrochemical device, reduce the minimum SOC level that can be effectively discharged, and improve the available discharge depth of the electrochemical device.
[0052] In some embodiments, the thickness ratio of the negative electrode active material layer to the thickness of the negative electrode sheet is 90% to 95%, for example, it can be 90%, 91%, 92%, 93%, 94%, 95%. Such a design combined with the aforementioned design of the linear recess can further optimize the available discharge depth of the electrochemical device, thereby reducing the minimum remaining charge (SOC) level required during the effective discharge process of the electrochemical device, and thus significantly enhancing the power supply capacity of the electrochemical device. The thickness of the negative electrode active material layer is calculated based on the total thickness of the negative electrode active material layer. For example, when there are negative electrode active material layers on both sides of the negative electrode current collector, the thickness of the negative electrode active material layer is calculated as the sum of the thicknesses of the two negative electrode active material layers.
[0053] In some embodiments, the surface resistance of the negative electrode sheet is R, with the unit of mΩ, and the electrochemical device satisfies Δm / R ≤ 0.2, for example, it can be 0.01, 0.05, 0.1, 0.15, 0.2. The surface resistance R of the negative electrode sheet is a strongly correlated factor determining the available discharge depth of the electrochemical device, which is mainly affected by the composition and particle size of the active material used, the conductive agent, and the binder. When this relational expression is satisfied, the low-temperature charge and discharge performance and low-temperature cycle performance of the electrochemical device can be further improved. When Δm / R is too large, it means that the surface density of the diaphragm coating layer is too large and the coating amount is too much, which is likely to cause the phenomenon of sol-gel plugging holes during the electrolyte immersion process, hinder the ion transport efficiency, and affect the charge and discharge ability of the electrochemical device.
[0054] In some embodiments, R is 10 to 60, for example, it can be 10, 20, 30, 40, 50, 60. When the surface resistance of the negative electrode sheet is in the range of 10 to 60 mΩ, it is beneficial for the electrochemical device to discharge, and can improve the low-temperature charge and discharge performance and low-temperature cycle performance of the electrochemical device. When R is too large, the power loss during the charge and discharge process of the battery increases, reducing the charge and discharge efficiency of the battery; when R is too small, the current density during the charge and discharge process of the battery will be too high, accelerating the aging and degradation of the battery materials.
[0055] In some embodiments, the thickness of the negative electrode sheet is 70 μm to 120 μm, for example, it can be 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm.
[0056] In some embodiments, the distance between adjacent linear recesses is 0.8 mm to 5 mm, for example, it can be 0.8 mm, 11.5 mm, 22.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm.
[0057] In some embodiments, the silicon-based material includes at least one of elemental silicon, silicon oxide compound (SiO x , 0 < x < 2), silicon-carbon material, silicon-nitrogen material, silicon alloy (such as silicon-magnesium alloy, silicon-lithium alloy, etc.).
[0058] In some embodiments, the negative electrode active material further comprises a carbon-based material, and the carbon-based material comprises at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.
[0059] In some embodiments, the negative electrode active material layer further comprises a conductive agent and a binder. In one embodiment, the conductive agent comprises at least one of conductive carbon black (such as Super-P), acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder, and carbon fiber. In one embodiment, the binder comprises at least one of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polytetrafluoroethylene, and polyethylene oxide.
[0060] In some embodiments, the negative electrode active material layer comprises 80-99.8 wt % of a negative electrode active material, 0.1-10 wt % of a conductive agent, and 0.1-10 wt % of a binder.
[0061] In some embodiments, the negative electrode active material layer comprises 90-99.6 wt % of the negative electrode active material, 0.2-5 wt % of the conductive agent, and 0.2-5 wt % of the binder.
[0062] The negative electrode current collector may be a negative electrode current collector commonly used in the art, such as copper foil or a composite current collector.
[0063] In one embodiment, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer located on at least one side surface of the positive electrode current collector.
[0064] In some embodiments, the positive electrode current collector may be a positive electrode current collector conventionally used in the art, such as aluminum foil or a composite current collector.
[0065] The positive electrode active layer is not particularly limited, and the positive electrode active layer may include components such as positive electrode active material, conductive agent, adhesive agent, etc. according to conventional compositions in the art. Among them, the positive electrode active material, conductive agent, adhesive agent, etc. components may be selected from conventional materials in the art, for example, the positive electrode active material may be selected from one or more of lithium nickelate, lithium titanate, lithium cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum, lithium iron phosphate, and lithium manganate, the conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene, and the adhesive may be selected from one or more of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.
[0066] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 80-99.8wt% of positive electrode active material, 0.1-10wt% of conductive agent, and 0.1-10wt% of binder.
[0067] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 90-99.6wt% of positive electrode active material, 0.2-5wt% of conductive agent, and 0.2-5wt% of binder.
[0068] The electrochemical device may further include an electrolyte, and the electrolyte may be a conventional electrolyte in the art, which will not be described in detail herein.
[0069] In some embodiments, the electrochemical device is a lithium ion battery, such as a lithium ion secondary battery.
[0070] If not otherwise specified, other options for the electrochemical device are conventional options in the art. The electrochemical device can be assembled in a conventional manner in the art.
[0071] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0072] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0073] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.
[0074] Example 1
[0075] (1) Diaphragm preparation
[0076] like Figure 1 As shown, the diaphragm includes a base film 11 and a ceramic layer 12 located on one surface of the base film 11, and a coating layer 13 located on the surface of the base film 11 away from the ceramic layer 12. The ceramic layer 12 includes a plurality of stripes distributed at intervals and a plurality of spacing areas located between adjacent stripes. The preparation method of the diaphragm is as follows.
[0077] The ceramic material, binder, dispersant and solvent are mixed to obtain ceramic slurry; the ceramic slurry is coated on one side of the base film layer by roller coating, and after high-temperature baking, a base film layer coated with a ceramic layer on one side is obtained; a rubber coating layer is coated on the other side of the ceramic surface to obtain a finished diaphragm.
[0078] The base film is a polyethylene microporous film, the thickness of the base film is 7 μm, the needle puncture strength is 300 gf, the elongation at break in the TD direction of the base film is 120%, and the elongation at break in the MD direction of the base film is 150%.
[0079] The ceramic material is boehmite, and Dv50 is 1 μm. The binder is polymethyl methacrylate, the dispersant is ethylene oxide, and the solvent is water; the mass ratio of the ceramic material, the binder, the dispersant, and the solvent is 35:4:1:60. The stripe width of the ceramic layer is 50 μm, the width of the spacer is 25 μm, the coating thickness is 1.5 μm, and the peel strength between the ceramic layer and the base film is 120 N / m. That is, A1 is 50, A2 is 25, and A is 2.
[0080] The coating layer is prepared using polymethyl methacrylate, the thickness of the coating layer is 1 μm, and the average particle size of the polymethyl methacrylate particles is 0.8 μm. The difference in surface density of the coating on both sides of the base film is 0 g / m 2 , that is, Δm is 0.
[0081] (2) Preparation of positive electrode
[0082] First, lithium cobalt oxide is used as an active material and mixed with Super-P conductive agent and activated carbon in a mass ratio of 1:1. Then, PVDF is added as a binder, and the active material, conductive agent and binder are dissolved in N-methylpyrrolidone solvent in a mass ratio of 97.5:1.35:1.15 to ensure uniform mixing. After that, the obtained positive electrode slurry is evenly coated on both sides of the aluminum foil current collector and dried to form a positive electrode film. Finally, the production of lithium-ion battery positive electrode sheets is completed through the steps of cold pressing, cutting into sheets and welding electrode ears.
[0083] (3) Preparation of negative electrode sheet
[0084] The silicon-carbon material is used as the negative electrode active material. The silicon content in the negative electrode active material is 4%. The silicon in the silicon-carbon material exists in the form of silicon particles. The average particle size of the silicon particles is D si The negative electrode active material is mixed with Super-P conductive agent, CMC thickener and SBR binder in a mass ratio of 97.1:0.6:1:1.2, and then dispersed in deionized water and stirred thoroughly to form a negative electrode slurry. Then, the negative electrode slurry is evenly coated on both sides of the copper foil current collector and dried to form a negative electrode film. Finally, the negative electrode sheet is prepared by cold pressing, cutting into sheets, laser wire bonding and welding electrode ears. Among them, D Si / A is 15.
[0085] In the negative electrode sheet, laser marking forms a linear recess on the surface of the negative electrode active material layer of the negative electrode sheet. The width of the linear recess is B1μm, and the depth of the linear recess is B2μm, wherein B1 is 90, B2 is 15, B=B1 / B2=6; A×B is 12; and the spacing between adjacent linear recesses is 2.5mm.
[0086] The surface resistance of the negative electrode sheet is 35 mΩ, and Δm / R is 0. The total thickness of the two negative electrode active material layers is 70 μm, and the thickness of the negative electrode sheet is 75 μm, that is, the thickness of the negative electrode active material layer accounts for 93% of the thickness of the negative electrode sheet.
[0087] (4) Preparation of electrolyte
[0088] Lithium hexafluorophosphate (LiPF 6 ) as a lithium salt, ethylene carbonate, diethyl carbonate, methyl ethyl carbonate and vinylene carbonate were mixed in a mass ratio of 8:85:5:2 to form a mixed solvent. Subsequently, the lithium salt and the solvent were mixed in a mass ratio of 8:92 to obtain an electrolyte.
[0089] (5) Preparation of lithium-ion batteries
[0090] The prepared positive electrode sheet, negative electrode sheet and separator are wound and assembled into a winding core, and after drying, liquid injection and packaging, a lithium-ion battery is obtained. Among them, the ceramic layer in the separator is adjacent to the positive electrode sheet, and the glue coating layer is adjacent to the negative electrode sheet.
[0091] Example 2 and Comparative Example 1
[0092] The operation is performed according to the method described in Example 1, except that at least one of A1, A2, B1 and B2 is different, as shown in Table 1.
[0093] In the prepared lithium battery, the difference in surface density of the coating on both sides of the base film is 2g / m 2 Within, that is, Δm≤2, the surface resistance R of the negative electrode sheet is in the range of 15 to 40mΩ, and Δm / R≤0.1.
[0094] Example 3 Group
[0095] The operation was carried out according to the method described in Example 1, except that D Si The details are shown in Table 1.
[0096] Table 1
[0097]
[0098]
[0099] Example 4
[0100] The operation was performed in accordance with the method described in Example 1, except that at least one of H, the particle size Dv50 of the ceramic material, the spacing between adjacent linear recesses, and the mass content of silicon in the negative electrode active material was different, as shown in Table 2.
[0101] Table 2
[0102] serial number H / μm Dv50 / μm Pitch / mm Silicon content Δm R Δm / R Example 1 1.5 1 2.5 4% 0 35 0 Example 4-1 0.5 0.3 1 * 1.7 20 0.08 Example 4-2 1 0.7 * * 0.8 20 0.04 Example 4-3 3 1.5 * * 2.5 20 0.13 Example 4-4 6 3 * * 7.5 20 0.38 Embodiment 4-5 3 * 6 8% 2.5 65 0.04 Embodiment 4-6 3 * 4 15% 2.5 17 0.15 Embodiment 4-7 3 * 1 20% 2.5 12 0.21 Embodiment 4-8 3 * 0.5 25% 2.5 8 0.31
[0103] Example 4
[0104] The operation was carried out according to the method described in Example 1, except that the type of base film was different. Its property parameters are shown in Table 3.
[0105] Table 3
[0106]
[0107]
[0108] Test Case
[0109] The performance of the lithium-ion batteries prepared in the examples and comparative examples was measured. The specific method is as follows. The results are shown in Table 4.
[0110] (1) Minimum remaining capacity (SOC) test for effective discharge
[0111] Wrap the lithium-ion battery with foam and monitor the surface temperature of the lithium-ion battery. ① Adjust the furnace temperature to 25℃ and leave it for 5min; ② Discharge at 0.5C to the lower limit voltage; ③ Leave it for 15min; ④ Charge at 1.8C constant current to the upper limit voltage, with a cut-off current of 0.05C; Leave it for 30min; ⑤ Cycle steps 2 to 4 to make C0; ⑥ Adjust the furnace temperature to 0℃ and leave it for 120min; ⑦ Discharge at 7.5C constant current for 15s, with a sampling frequency of 100ms; ⑧ Leave it for 30min; ⑨ Adjust the discharge at 1C to the target SOC; ⑩ Leave it for 90min; Repeat steps 7 to 10 and change the SOC to the required SOC at the temperature until the discharge cut-off voltage is lower than the lower limit voltage at 0°C and SOC, and record the minimum remaining capacity (SOC) for effective discharge.
[0112] (2) Cyclic performance test
[0113] The initial thickness and initial capacity of the lithium-ion battery were tested at 10°C, then discharged at 10C to the lower cut-off voltage; left standing for 30 minutes; charged at 3C to the upper cut-off voltage, constant voltage to 0.05C; left standing for 5 minutes; then cycled for 600T, paused after every 100T, and then tested the thickness and capacity of the lithium-ion battery in the fully charged state.
[0114] Thickness expansion rate = (battery thickness after different cycles - initial thickness) / initial thickness × 100%.
[0115] Capacity retention rate = battery capacity after different cycles / initial capacity × 100%.
[0116] (3) Rate performance test
[0117] Place the lithium-ion battery at 25℃ for 5 minutes; discharge at 0.5C to 2.5V, charge at 1C to 4.2V, maintain constant voltage to 0.05C, discharge at 0.2C to obtain the initial capacity; place for 30min; charge at 1C to 100% SOC at room temperature; place for 15 minutes, stand at 0℃ for 2h, discharge at 10C to the lower limit voltage, and record the discharge capacity. Calculate the 10C discharge capacity retention rate of the battery by the following formula.
[0118] 10C discharge capacity retention rate (%) = discharge capacity / initial capacity × 100%.
[0119] Table 4
[0120]
[0121]
[0122] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet and a separator located between the positive and negative electrode sheets; The diaphragm comprises a base film and a ceramic layer disposed on at least one side of the base film, wherein the ceramic layer comprises a plurality of stripes distributed at intervals and a plurality of spacing areas located between adjacent stripes, wherein the width of the stripes is A1 μm, the width of the spacing area is A2 μm, and A is A1 / A2; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein a plurality of linear recesses are formed on the surface of the negative electrode active material layer on at least one side of the negative electrode sheet away from the negative electrode current collector, wherein the width of the linear recess is B1 μm, the depth of the linear recess is B2 μm, and B is B1 / B2; The electrochemical device satisfies the relationship 3≤B≤11 and 5≤A×B≤50.
2. The electrochemical device according to claim 1, characterized in that A1 is 25 to 100; and / or A2 is 6.7 to 50; and / or B1 is 80-100; and / or B2 is 10 to 20; and / or A is 1 to 5.
3. The electrochemical device according to claim 1, characterized in that The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material, in which silicon exists in the form of silicon particles; the average particle size D of the silicon particles Si The unit is nm and satisfies: 5≤D Si / A≤30.
4. The electrochemical device according to claim 3, characterized in that The average particle size D of the silicon particles Si 10 to 60; and / or The silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys; and / or The content of silicon in the negative electrode active material is 3-20 wt %.
5. The electrochemical device according to any one of claims 1 to 4, characterized in that: The diaphragm further comprises a coating layer located on the surface of the base film and / or the surface of the ceramic layer; Preferably, the difference in surface density of the coating on both sides of the base film is Δm, expressed in g / m 2 , Δm≤4; Preferably, the rubber coating layer comprises polymer particles.
6. The electrochemical device according to claim 5, characterized in that The surface resistance of the negative electrode sheet is R, in units of mΩ, and the electrochemical device satisfies Δm / R≤0.2; Preferably, R is 10-60.
7. The electrochemical device according to any one of claims 1 to 4, characterized in that: The thickness of the negative electrode sheet is 70 μm to 120 μm; and / or The distance between adjacent linear recesses is 0.8 mm to 5 mm.
8. The electrochemical device according to any one of claims 1 to 4, characterized in that: The thickness H of the stripes in the ceramic layer of the diaphragm is 0.5 μm to 5 μm.
9. The electrochemical device according to any one of claims 1 to 4, characterized in that: The ceramic layer comprises 40 wt% to 96 wt% of a ceramic material, 3 wt% to 60 wt% of a binder and optionally 0.7 wt% to 3 wt% of a dispersant; Preferably, the ceramic material includes at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silicon dioxide, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, cerium oxide, zirconium titanate, barium titanate, and magnesium fluoride. Preferably, the particle size Dv50 of the ceramic material is 0.1 μm to 2.5 μm.
10. The electrochemical device according to any one of claims 1 to 4, characterized in that: The thickness of the base film is 4 μm to 20 μm; and / or The base film is a woven film, a non-woven film, a polyolefin film or a separator paper, and preferably, the material of the polyolefin film includes at least one of polyethylene and polypropylene; and / or The elongation at break of the base film in the TD direction is 20% to 200%; and / or The elongation at break of the base film in the MD direction is 50% to 300%; and / or The puncture strength of the basement membrane is 100 gf to 600 gf; and / or The peel strength between the ceramic layer and the base film is 30 to 200 N / m.
Citation Information
Patent Citations
Composite diaphragm and application thereof
CN116315457A
Negative plate and battery
CN118335903A
Ceramic cross grain coated diaphragm
CN208955083U
Battery and method of manufacturing the same
US20210036313A1
Cited By
Electrochemical device
WO2026139070A1